2011
DOI: 10.5539/ijef.v3n6p107
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of Tax Office Automation System (VEDOP) By Employees: Factorial Validation of Turkish Adapted Technology Acceptance Model (TAM)

Abstract: In this study, Davis's (1989) The Technology Acceptance Model (TAM) is used as a theoretical framework to extend and complement extant tax officials by acceptance of technological components of Tax Office Automation System (VEDOP) in Turkey. Relying on the basic TAM model, we examine the extent to which perceived usefulness (PU), perceived ease of use (PE), and attitudes (AT) toward VEDOP affect behavior intentions (BI). The data set of the study was obtained from the survey applied to 185 individual tax offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Legris et al (2003) emphasize the importance of efforts to develop models in order to explain more broadly about the acceptance of an IT (Taylor&Todd, 1995). Several previous research adopt TAM as a basis to analyze the acceptance of e-system especially e-filing (Wang, 2002;Chan et al, 2004;Chang, 2005;Fu et al, 2006, Hung et al, 2006Lu et al, 2008;Suki&Ramayah, 2010;Cakmak et al, 2011;Shin et al, 2018;Hasan et al, 2019) The objective of this study is to assess user attitudes toward e-filing (behavior toward use) that are influenced by perceived ease of use, perceived usefulness, and its effect on interest in the use of e-filing (behavioral intention to use) as well as its impact on the practical use of e-filing system (actual usage). The theory that underlies in this study is the Technology Acceptance Modelwhich is an advancement of the Reasoned Action Theory as reflected in Figure…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Legris et al (2003) emphasize the importance of efforts to develop models in order to explain more broadly about the acceptance of an IT (Taylor&Todd, 1995). Several previous research adopt TAM as a basis to analyze the acceptance of e-system especially e-filing (Wang, 2002;Chan et al, 2004;Chang, 2005;Fu et al, 2006, Hung et al, 2006Lu et al, 2008;Suki&Ramayah, 2010;Cakmak et al, 2011;Shin et al, 2018;Hasan et al, 2019) The objective of this study is to assess user attitudes toward e-filing (behavior toward use) that are influenced by perceived ease of use, perceived usefulness, and its effect on interest in the use of e-filing (behavioral intention to use) as well as its impact on the practical use of e-filing system (actual usage). The theory that underlies in this study is the Technology Acceptance Modelwhich is an advancement of the Reasoned Action Theory as reflected in Figure…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Significant P-value (p<0.01) with positive (+.328) path co-efficient supports the above hypothesis. A study has found out that the perception of the HR Professionals regarding the usefulness of a particular technology has a deep impact on their attitude for the adoption of that particular technology (Cakmak, et al, 2011). This study was conducted in Turkey regarding the assessment of the acceptance level of the Tax Office Automation System (VEDOP) amongst the HR Professionals.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Both of these perceptions affect the Attitude Toward Using Individuals to the use of technology [12]. This model describes the driving factors underlying the behaviour of users of information technology to the acceptance of information technology of adoption of information technology [13].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%